Determining critical factors of location choice of cross-border merger and acquisition : the case of Chinese firms / Feng Zhang and Guohua Jiang - Guohua, Jiang; Jiang, Guohua (Faculty of Business Management, 2013)
This paper examines the location decision on cross-border mergers and acquisitions (M&As) of Chinese multinational corporations (MNCs). Logistic regression technique is employed to test the motives of Chinese MNCs’ M&As between 2004 and 2006 in developed countries vs. developing countries. We find that strategic asset-seeking, in particular technology-seeking, is the major reason for Chinese firms to merge or acquire firms from developed countries, whereas their M&As in developing countries are largely motivated by resource-seeking. A closer examination suggests that technology-seeking M&As might be motivated not only by an objective to learn from developed country firms but also by a desire to prevent the competing firms from getting ahead in the technology race, especially firms from other developing countries. Findings of this study have implications for policy makers of catching up economies in assisting firms’ learning and international competition.